Cost of poor health to the labour market returns to education in Australia – another pathway for socio-economic inequality - Doan, Tinh; Strazdins, Lyndall; Leach, Liana (My University, 2020)
While several studies have estimated returns to education in Australia, there is limited evidence regarding the influence of health on the returns. This paper identifies how health affects returns to education in the labour market using the Heckman selection bias-corrected model. We measured health status using a self-rated health item with five response categories ‘poor, fair, good, very good, and excellent’. The findings show that poor health or being unhealthy (defined as ‘poor’ or ‘fair’) interacts with education, such that the benefits of education (i.e. higher hourly wage rate) are curtailed in those with health problems; the adverse effect is stronger for those in lower skilled jobs. The estimated returns to an additional year of schooling on average over 2001–2017 is 7.43% and 6.88% for the healthy and unhealthy groups, respectively. Thus, the return for workers with poor health is 7.4% lower than the return for healthier workers (for each additional year of schooling). This gap in the returns is equivalent to a productivity loss of about $19–25 billion per year. The lower returns to education for workers with poor health likely results from lower productivity while at work rather than loss of working days as the estimate is based on an hourly wage rate (rather than days or hours absent from work). These lower returns may also be explained by unhealthy workers accepting lower paid jobs given the same levels of experience, skills and education that healthier counterparts have. The cost of poor health to labour market returns is further amplified in low-skilled occupations, a process which is likely to exacerbate socio-economic inequalities and undercut social mobility.
The European Journal of Health Economics
Keywords: Health and wellbeing; Labour market